THE SHADOW OF COLONIALISM IN A SERIES OF CONFLICTS UNTIL WORLD WAR IN AFRICA - Adrian Farsyah; Anan Firnandi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research discusses the impact of Western colonialism on the dynamics of conflict and crisis in African regions from the 19th century to post-World War II. Using a historical-qualitative approach supported by JA Hobson's liberal imperialism theory, this study examines how competition between colonial powers such as Britain, France, and Germany not only divided the African region but also strengthened the structure of political and economic domination that led to a series of international crises, such as the Fashoda Crisis, Morocco Crisis I and II, and the prolonged conflict in Ethiopia. Besides being a target for military and economic expansion, Africa was also used as a stage for global power struggles during the World Wars, making it a logistical and resource base for war. The findings show that colonialism not only created structural inequalities but also queathed patterns of ongoing conflict into the contemporary era. Therefore, strengthening local historical narratives and revitalizing the role of regional institutions such as the African Union are crucial to building identity and political independence amid complex colonial legacies. This research is expected to contribute to the understanding of the history of global conflict and become a reflective basis for peaceful resolution efforts in contemporary Africa.